Carbon-coated ferroferric oxide lithium ion battery negative electrode material and preparation method thereof

CN117985769BActive Publication Date: 2026-10-13FUDAN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410016424.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-05
Publication Date
2026-10-13
Estimated Expiration
2044-01-05

AI Technical Summary

Technical Problem

[0017]本发明的目的是提供一种碳包覆四氧化三铁锂离子电池负极材料及其制备方法,以解决Fe3O4负极材料导电性能较差,以及电池在充放电循环过程中其比容量衰减过快等问题

Benefits of technology

[0030](1)由于Fe3O4超薄纳米片具有巨大的比表面积和出色的电荷传输率,有助于扩大电极与电解质之间的反应界面,从而促进电荷传递、提高电池的导电性和充放电性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117985769B_ABST
    Figure CN117985769B_ABST
Patent Text Reader

Abstract

This invention belongs to the field of energy storage materials technology, specifically a carbon-coated iron tetroxide (Fe3O4) lithium-ion battery anode material and its preparation method. The preparation steps include: preparing the precursor iron hydroxyl oxide (ITO) using a hydrothermal method; modifying the ITO with dopamine; and calcining the polydopamine-modified ITO in a tube furnace under an inert atmosphere to obtain carbon-coated metal oxide nanoparticles with a particle size of 50-250 nm and a thickness of 4-7 nm. Lithium-ion coin cells prepared with this anode material exhibit excellent performance in charge-discharge tests, achieving a current density of 200 mA g / g. ‑1 After 120 cycles, the discharge specific capacity can be maintained at 1629 mAh g. ‑1 At a current density of 20 A g ‑1 After 3000 cycles, the discharge specific capacity still remains at 623.6 mAh g. ‑1 This lithium-ion battery anode material exhibits high reversible capacity and good cycle stability. The preparation method is simple to operate and is safe and non-toxic.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of energy storage materials technology, specifically relating to a carbon-coated iron tetroxide lithium-ion battery anode material and its preparation method. Background Technology

[0002] Lithium-ion secondary batteries are favored for their high voltage, high specific energy, wide operating temperature range, low self-discharge rate, no memory effect and environmental friendliness. At present, lithium-ion batteries are widely used in portable devices such as mobile phones, laptops, camcorders and cameras, and will be more widely used in electric vehicles, satellites and military fields in the future [1].

[0003] In the field of lithium battery anode materials, carbon anode materials commonly used in traditional industry have a capacity of 372 mAh g. -1 The theoretical capacity[2]. However, transition metal oxides in novel anode materials have higher theoretical capacities, far exceeding those of carbon anode materials. Among them, iron(III) oxide (Fe3O4) not only has a high theoretical capacity (924 mAh g), but also has a high theoretical capacity (924 mAh g). -1 Fe3O4 has advantages such as high safety voltage, good conductivity, low cost, abundant natural resources and environmental protection[3]. However, the application of Fe3O4 in lithium-ion batteries is limited by its large volume change and poor cycle performance caused by agglomeration during lithium insertion / de-lithiation[4]. In order to further improve the electrochemical performance of Fe3O4, researchers have adopted a variety of modification methods, including the preparation of nano-sized Fe3O4, carbon-coated Fe3O4 and Fe3O4 / graphene composite materials[5-7]. Nanomaterials, especially two-dimensional nanosheets, have a large specific surface area and a short diffusion path, which helps to improve electrochemical performance[8]. The carbon coating layer can effectively alleviate the large volume change of active materials during battery charging and discharging and avoid the agglomeration of active materials. At present, the preparation methods of carbon-coated Fe3O4 nanocomposites mainly include hydrothermal method, solvothermal method, ball milling method, co-precipitation method and high temperature solid phase method[9-3]. Compared with the traditional hydrothermal method, the high temperature solid phase method has advantages such as low cost, simple preparation process, high yield and easy industrial production.

[0004] [1] Kim T, Song W, Son DY, et al. Lithium-ion batteries: outlook on present, future, and hybridized technologies [J]. Journal of materials chemistryA, 2019, 7(7): 2942-2964.

[0005] [2]Wang Y,Deng Y,Qu Q,et al.Ultrahigh-capacity organic anode withhigh-rate capability and long cycle life for lithium-ion batteries[J].ACSEnergy Letters,2017,2(9):2140-2148.

[0006] [3]Liu M,Jin H,Uchaker E,et al.One-pot synthesis of in-situ carbon-coated Fe3O4as a long-life lithium-ion battery anode[J].Nanotechnology,2017,28(15):155603.

[0007] [4]Hsieh C T,Lin J Y,Mo C Y.Improved storage capacity and ratecapability of Fe3O4–graphene anodes for lithium-ion batteries[J].Electrochimica Acta,2011,58:119-124.

[0008] [5]Behera S K.Facile synthesis and electrochemical properties ofFe3O4nanoparticles for Liion battery anode[J].Journal of Power Sources,2011,196(20):8669-8674.

[0009] [6]Yu Y,Zhu Y,Gong H,et al.Fe3O4nanoparticles embedded in carbon-framework as anode material for high performance lithium-ion batteries[J].Electrochimica acta,2012,83:53-58.

[0010] [7]Gu S,Zhu A.Graphene nanosheets loaded Fe3O4nanoparticles as apromising anode material for lithium ion batteries[J].Journal of Alloys andCompounds,2020,813:152160.

[0011] [8]Li Z,Zhao H,Wang J,et al.3D heterostructure Fe3O4 / Ni / C nanoplatearrays on Ni foam as binder-free anode for high performance lithium-ionbattery[J].Electrochimica Acta,2015,182:398-405.

[0012] [9]Li H,Wang J,Li Y,et al.Hierarchical sandwiched Fe3O4@C / Graphenecomposite as anode material for lithium-ion batteries[J].Journal ofElectroanalytical Chemistry,2019,847:113240.

[0013]

[10] Gu S,Zhu A.Graphene nanosheets loaded Fe3O4nanoparticles as apromising anode material for lithium ion batteries[J].Journal of Alloys andCompounds,2020,813:152160.

[0014]

[11] Liu H,Luo S,Hu D,et al.Design and synthesis of carbon-coatedα-Fe2O3@Fe3O4heterostructured as anode materials for lithium ion batteries[J].Applied Surface Science,2019,495:143590.

[0015]

[12] Ai Q, Yuan Z, Huang R, et al. One-pot co-precipitation synthesis ofFe3O4nanoparticles embedded in 3D carbonaceous matrix as anode for lithium ionbatteries[J]. Journal of Materials Science, 2019, 54(5): 4212-4224.

[0016]

[13] Chen X, Zhu Summary of the Invention

[0017] The purpose of this invention is to provide a carbon-coated Fe3O4 lithium-ion battery anode material and its preparation method, in order to solve the problems of poor conductivity of Fe3O4 anode material and excessively rapid capacity decay during battery charge-discharge cycles.

[0018] The present invention provides a method for preparing carbon-coated iron tetroxide (Fe3O4) lithium-ion battery anode material, comprising: preparing a precursor iron hydroxyl oxide (ITO) using a hydrothermal method; modifying the ITO with dopamine; and calcining the polydopamine-modified ITO in a tube furnace under an inert atmosphere to obtain carbon-coated metal oxide nanoparticles. The specific steps are as follows:

[0019] (1) Preparation of ferric hydroxide:

[0020] Using deionized water as a solvent, Fe salt was dissolved in the deionized water as the Fe source. Sodium sulfate and polyethyleneimine were added as surfactants. A hydrothermal reaction was carried out. The product was centrifuged, washed, and dried in a vacuum to obtain iron hydroxy oxide powder, denoted as FeOOH.

[0021] The specific operating procedure is as follows: Fe salt and sodium sulfate are dissolved in deionized water at room temperature (20-25℃); polyethyleneimine is gradually added to the Fe salt solution, and after stirring for 20-60 minutes, the mixture is transferred to a reaction vessel; the mixture is heated to 130-155℃ for 8-24 hours. The product is centrifuged and washed repeatedly with deionized water, and finally vacuum dried at 20-80℃ for 4-16 hours to obtain brown iron hydroxide powder.

[0022] (2) Preparation of Fe3O4@C nanosheets:

[0023] FeOOH was uniformly dispersed in deionized water as a solvent; the product, Fe3O4@C nanosheets, was obtained through dopamine coating and carbonization-reduction reaction under an inert atmosphere.

[0024] The specific operating procedure is as follows:

[0025] FeOOH was uniformly dispersed in deionized water at room temperature (20-25℃). The solution was adjusted to pH 8.5 using Bis-Tris buffer solution, and then dopamine hydrochloride solution was added, with a mass ratio of dopamine hydrochloride to FeOOH of 1:1-1:5. The mixture was stirred continuously for 18-24 hours. The product was transferred to centrifuge tubes and washed multiple times with deionized water. The product was then transferred to a vacuum drying oven and dried at 20-80℃ for 10-16 hours to obtain a brown powder, i.e., dopamine-coated iron hydroxyl oxide, denoted as FeOOH@dopa. The FeOOH@dopa product was placed in a ceramic boat and heated to 400-600℃ at a heating rate of 1-5℃ / min under a reducing atmosphere, and sintered at this temperature for 3-6 hours. After natural cooling, a black solid product was obtained, denoted as Fe3O4@C.

[0026] In step (1), the Fe salt is FeCl3, Fe(NO3)2 or their hydrates; preferably FeCl3·6H2O. Sodium sulfate and polyethyleneimine are used as additives.

[0027] In step (2), the reducing atmosphere is Ar or N2, and the gas flow rate is controlled to be 50-150 mL / min.

[0028] The Fe3O4@C prepared by this invention has a particle size of 50-250 nm and a thickness of 4-7 nm; it exhibits excellent cycling performance; Fe3O4@C at 20A g -1 At current density, it can achieve high capacity and long cycle life, and can be used as a negative electrode material for lithium-ion batteries; while maintaining high specific capacity, the negative electrode material for lithium-ion batteries further improves its cycle stability.

[0029] The present invention has the following advantages over the prior art:

[0030] (1) Due to the large specific surface area and excellent charge transport rate of Fe3O4 ultrathin nanosheets, it helps to expand the reaction interface between the electrode and the electrolyte, thereby promoting charge transfer and improving the conductivity and charge-discharge performance of the battery.

[0031] (2) Due to the excellent conductivity of carbon, the Fe3O4 / carbon lithium-ion battery composite anode material can easily conduct charge carriers during charging and discharging, and can effectively alleviate volume changes, thereby maintaining the stability of the structure.

[0032] (3) The preparation process is simple, the synthesis is convenient, the yield is high and the repeatability is good, so it is very suitable for use in actual lithium-ion battery applications and has the feasibility of large-scale production. Attached Figure Description

[0033] Figure 1 The image shows the XRD pattern of the iron hydroxyl oxide material obtained in Example 1 of this invention.

[0034] Figure 2 This is a SEM image of the iron hydroxyl oxide material obtained in Example 1 of the present invention.

[0035] Figure 3 This is a TEM image of the iron hydroxyl oxide material obtained in Example 1 of the present invention.

[0036] Figure 4 The image shows the XRD pattern of the iron oxide material obtained in Example 1 of this invention.

[0037] Figure 5 This is a SEM image of the iron oxide material obtained in Example 1 of the present invention.

[0038] Figure 6 This is a TEM image of the iron oxide material obtained in Example 1 of the present invention.

[0039] Figure 7 The Fe3O4@C lithium-ion battery composite anode material obtained in Example 1 of this invention is used as a lithium-ion battery anode material at 500 mAg. -1 The charge / discharge performance diagram at the current density.

[0040] Figure 8 The Fe3O4@C lithium-ion battery composite anode material obtained in Example 1 of this invention is used as a lithium-ion battery anode material at 20Ag. -1 The charge / discharge performance diagram at the current density. Detailed Implementation

[0041] The present invention will be further illustrated by the following examples, but these examples do not limit the scope of the invention.

[0042] Example 1:

[0043] (1) Preparation of ferric hydroxide

[0044] At room temperature (25°C), 3 mmol FeCl3·6H2O and 3 mmol Na2SO4 were dissolved in 75 mL of deionized water and stirred for 10 minutes. Then, 0.006 mmol polyethyleneimine was added, and stirring continued for 30 minutes. The mixture was transferred to a reaction vessel and heated to 150°C for 20 hours. The product was separated by centrifugation, washed three times with deionized water, and then vacuum dried at 60°C for 12 hours to obtain a brown powder. X-ray powder diffraction (XRD) analysis showed that the product was pure iron hydroxide, free of any other impurities (see details). Figure 1 Scanning electron microscopy (SEM) images show iron hydroxyoxide as thin flakes, ranging in length from 50 to 250 nm (see details). Figure 2 The transmission electron microscope (TEM) image further shows that iron hydroxyaoxide is in the form of thin sheets, with a thickness of approximately 4.8 nm (see details). Figure 3 ).

[0045] (2) Preparation of Fe3O4@C nanosheets:

[0046] At room temperature (20-25℃), 80 mg FeOOH was dispersed in 50 ml of deionized water. The pH of the solution was adjusted to 8.5 using Bis-Tris solution, and then 25 ml (2 mg / ml) of dopamine hydrochloride solution was added, with continuous stirring for 48 hours. The product was transferred to centrifuge tubes and washed multiple times with deionized water. The final product was then transferred to a vacuum drying oven and dried at 60℃ for 12 hours, yielding a grayish-black powder, which was dopamine-coated iron hydroxyl oxide. Subsequently, this product was placed in a ceramic boat and heated to 500℃ under an argon atmosphere for 4 hours. After natural cooling, a black Fe3O4@C solid powder was obtained. XRD analysis showed that the obtained product was pure iron(III) oxide, without any other impurities (such as...). Figure 4 As shown in the SEM image, iron(III) oxide appears as thin flakes, with a length of 50-250 nm (as shown in the image). Figure 5 As shown in the TEM image, the carbon-coated iron(III) oxide is in the form of thin flakes, with a thickness of 5.1 nm (as shown). Figure 6 (As shown).

[0047] (3) The Fe3O4@C lithium-ion battery composite negative electrode material prepared in this embodiment was assembled with lithium sheets into a coin cell. At 25°C, at 200 mA g... -1When subjected to constant current charge-discharge testing in the range of 0.01-3.0V at a current density, its reversible capacity after 120 cycles is 1629 mAh g. -1 At 25°C, with 20A g -1 When subjected to constant current charge-discharge testing in the range of 0.01-3.0V at a current density, its reversible capacity after 3000 cycles is 623.6 mAh g. -1 .

[0048] Example 2:

[0049] Polydopamine-modified iron hydroxyl oxide was prepared using the same method as steps (1) and (2) in Example 1. 100 mg of dopamine-modified iron hydroxyl oxide powder was placed in a ceramic boat, and the temperature was raised to 400 °C and held for 4 hours under an Ar atmosphere. After the reaction was complete, the product was cooled to room temperature and removed as a black product. Further XRD analysis showed that the Fe3O4@C composite material was prepared in a similar manner to that in Example 1.

[0050] The Fe3O4@C lithium-ion battery composite anode material prepared in this embodiment was assembled with lithium sheets into a coin cell. At 25°C, at a rate of 200 mA g... -1 When subjected to constant current charge-discharge testing in the range of 0.01-3.0V at a current density, its reversible capacity after 120 cycles is 1210 mAh g. -1 At 25°C, under constant current charge-discharge testing at a current density of 20 A g⁻¹ in the range of 0.01–3.0 V, after 3000 cycles, its reversible capacity is 546.3 mAh g⁻¹. -1 .

[0051] Example 3:

[0052] Polydopamine-modified iron hydroxyl oxide was prepared using the same method as steps (1) and (2) in Example 1. 100 mg of dopamine-modified iron hydroxyl oxide powder was placed in a ceramic boat, and the mixture was heated to 500 °C and held at that temperature for 4 hours under an Ar atmosphere. After the reaction was complete, the mixture was cooled to room temperature and the black product was removed. Further XRD analysis showed that the Fe3O4@C composite material was prepared in a similar manner to that in Example 1.

[0053] The Fe3O4@C lithium-ion battery composite anode material prepared in this embodiment was assembled with lithium sheets into a coin cell. At 25°C, at a rate of 200 mA g... -1 When subjected to constant current charge-discharge testing in the range of 0.01-3.0V at a current density, its reversible capacity after 120 cycles is 1013 mAh g. -1 At 25°C, with 20A g -1When subjected to constant current charge-discharge testing in the range of 0.01-3.0V at a current density, its reversible capacity after 3000 cycles is 466.1 mAh g. -1 .

Claims

1. A method for preparing a carbon-coated iron tetroxide lithium-ion battery anode material, characterized in that, Iron hydroxyl oxide precursor was prepared by hydrothermal method; the iron hydroxyl oxide was modified with dopamine; the polydopamine-modified iron hydroxyl oxide was calcined in a tube furnace under an inert atmosphere to obtain carbon-coated metal oxide nanoparticles. The specific steps are as follows: (1) Preparation of iron hydroxyoxide: Fe salt was dissolved in deionized water as the Fe source, and sodium sulfate and polyethyleneimine were added as surfactants to carry out a hydrothermal reaction. The product was centrifuged and washed, and then dried in a vacuum to obtain iron hydroxy oxide powder, denoted as FeOOH. (2) Preparation of Fe3O4@C nanosheets: FeOOH was uniformly dispersed in deionized water; the product, Fe3O4@C nanosheets, was obtained through dopamine coating and carbonization-reduction reaction under an inert atmosphere. Step (1) The specific operation process is as follows: at room temperature, Fe salt and sodium sulfate are dissolved in deionized water; polyethyleneimine is gradually added to the Fe salt solution, and after stirring for 20-60 minutes, the mixture is transferred to a reaction vessel; the mixture is heated to 130-155℃ for 8-24 hours; the product is centrifuged and washed with deionized water multiple times, and then vacuum dried at 20-80℃ for 4-16 hours to obtain brown iron hydroxy oxide powder; In step (1), the Fe salt is FeCl3, Fe(NO3)2 or its hydrate; The specific operation process of step (2) is as follows: At room temperature, FeOOH is uniformly dispersed in deionized water; the solution is adjusted to pH=8.5 by Bis-Tris buffer solution, and then dopamine hydrochloride solution is added. The mass ratio of dopamine hydrochloride to FeOOH is 1:1-1:5; stirring is continued for 18-24 hours; the product is transferred to a centrifuge tube and washed by centrifugation multiple times with deionized water; the product is transferred to a vacuum drying oven and dried at 20-80℃ for 10-16 hours to obtain a brown powder, namely dopamine-coated iron hydroxy oxide, denoted as FeOOH@dopa; the FeOOH@dopa product is placed in a porcelain boat and heated to 400-600℃ at a heating rate of 1-5℃ / min under a reducing atmosphere, and sintered at a constant temperature for 4-6 hours. After it cools down naturally, a black solid product is obtained, which is Fe3O4@C; In step (2), the reducing atmosphere is Ar or N2, and the gas flow rate is controlled to be 50-150 mL / min.

2. The carbon-coated iron tetroxide lithium-ion battery anode material obtained by the preparation method described in claim 1 is a nanosheet with a particle size of 50-250 nm and a thickness of 4-7 nm.